Как Маша стала большой: [рассказы и сказки] / Е. А. Пермяк ; художник А. Шахгельдян - Пермяк Евгений Андреевич (Страна детства, 2006)
Экземпляры: ДБ (20070618) / Инвентарный номер: 38749 / Цена: 55.00 / Авт.знак: П 27 / ББК: 84(2Рос=Рус)6